Folate‐ and vitamin B12‐deficient diet during gestation and lactation alters cerebellar synapsin expression via impaired influence of estrogen nuclear receptor α. Issue 9 (27th May 2015) - Pourié, Grégory; Martin, Nicolas; Bossenmeyer‐Pourié, Carine; Akchiche, Nassila; Guéant‐Rodriguez, Rosa Maria; Geoffroy, Andréa; Jeannesson, Elise; Chehadeh, Sarah E1 Hajj; Mimoun, Khalid; Brachet, Patrick; Koziel, Violette; Alberto, Jean‐Marc; et al.
ABSTRACT: Deficiency in the methyl donors vitamin B12 and folate during pregnancy and postnatal life impairs proper brain development. We studied the consequences of this combined deficiency on cerebellum plasticity in offspring from rat mothers subjected to deficient diet during gestation and lactation and in rat neuroprogenitor cells expressing cerebellum markers. The major proteomic change in cerebellum of 21‐d‐old deprived females was a 2.2‐fold lower expression of synapsins, which was confirmed in neuroprogenitors cultivated in the deficient condition. A pathway analysis suggested that these proteomic changes were related to estrogen receptor a (ER‐α)/Src tyrosine kinase. The influence of impaired ER‐α pathway was confirmed by abnormal negative geotaxis test at d 19‐20 and decreased phsophorylation of synapsins in deprived females treated by ER‐α antagonist 1, 3‐ bis (4‐hydroxyphenyl)‐4‐methyl‐5‐[4‐(2‐piperidinylethoxy)phenol]‐1 H ‐pyrazole dihydrochloride (MPP). This effect was consistent with 2‐fold decreased expression and methylation of ER‐α and subsequent decreased ER‐α/PPAR‐γ coactivator 1 a (PGC‐1α) interaction in deficiency condition. The impaired ER‐α pathway led to decreased expression of synapsins through 2‐fold decreased EGR‐1/Zif‐268 transcription factor and to 1.7‐fold reduced Src‐dependent phosphorylation of synapsins. The treatment of neuroprogenitors with either MPP or PP1 (4‐(4'‐phenoxyani]ino)‐6, 7‐diniethoxyquinazoline, 6, 7‐dimethoxy‐N‐(4‐phenoxyphenyl)‐4‐quinazolinamine, SKI‐1, Src‐11) Src inhibitor produced similar effects. In conclusion, the deficiency during pregnancy and lactation impairs the expression of synapsins through a deregulation of ER‐α pathway.—Pourié, G., Martin, N., Bossenmeyer‐Pourié, C., Akchiche, N., Guéant‐Rodriguez, R. M., Geoffroy, A., Jeannesson, E., E1 Hajj Chehadeh, S., Mimoun, K., Brachet, P., Koziel, V., Alberto, J.‐M., Helle, D., Debard, R., Leininger, B., Daval, J.‐L., Guéant, J.‐L. Folate‐ and vitamin B12 ‐deficient diet during gestation and lactation alters cerebellar synapsin expression via impaired influence of estrogen nuclear receptor a. FASEB J. 29, 3713‐3725 (2015). www.fasebj.org